Large mesospheric ice particles at exceptionally high altitudes - L. Megner; M. Khaplanov; G. Baumgarten; J. Gumbel; J. Stegman; B. Strelnikov; S. Robertson (Annales Geophysicae, 2009)
We here report on the characteristics of exceptionally high Noctilucent clouds (NLC) that were detected with rocket photometers during the ECOMA/MASS campaign at Andøya, Norway 2007. The results from three separate flights are shown and discussed in connection to lidar measurements. Both the lidar measurements and the large difference between various rocket passages through the NLC show that the cloud layer was inhomogeneous on large scales. Two passages showed a particularly high, bright and vertically extended cloud, reaching to approximately 88 km. Long time series of lidar measurements show that NLC this high are very rare, only one NLC measurement out of thousand reaches above 87 km. The NLC is found to consist of three distinct layers. All three were bright enough to allow for particle size retrieval by phase function analysis, even though the lowest layer proved too horizontally inhomogeneous to obtain a trustworthy result. Large particles, corresponding to an effective radius of 50 nm, were observed both in the middle and top of the NLC. The present cloud does not comply with the conventional picture that NLC ice particles nucleate near the temperature minimum and grow to larger sizes as they sediment to lower altitudes. Strong up-welling, likely caused by gravity wave activity, is required to explain its characteristics.